RANCANG BANGUN PROTOTYPE PLTMH DENGAN TURBIN PELTON SEBAGAI MODUL PRAKTIKUM - Andhita Mahayana, I Gusti Putu; Jasa, Lie; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM, 2020)
Learned about the use of water resources as a micro hydro power plant is very important to be carried out by Electrical Engineering students at Udayana University. At this time at Convertion Energy Laboratory there was not been a practicum about Mycro Hydro Power Plan due to the unavailability of guide practicum module and micro hydro power plant prototypes. Therefore in this research was design and build a Prototype of Microhydro Power Plan wich had 18 buckets where had 5 cm width, 4,47 cm length, 1,6 height and the tickness was 0,28 cm. This prototype can made 4,5 L/s water discharge, 9,809 W Power, and the torque was 0,26 Nm . So that prototype had 1,48% efficiency. To make this prototype as a complete practicum module was arranged practicum guide modules that was explain abaout Characteristic of Micro Hydro Power Plan with Pelton Turbines.